Evaluation of Agricultural Accounting Software. Improved Decision Making. Third Edition Ashley C. Lovell, Comp. - Lovell, Ashley C. (Distributed by ERIC Clearinghouse, 1987)
Following a discussion of the evaluation criteria for choosing accounting software, this guide contains reviews of 27 accounting software programs that could be used by farm or ranch business managers. The information in the reviews was provided by the software vendors and covers the following points for each software package: general features, type, vendor evaluation, computing considerations, chart of accounts, printed reports, general ledger, enterprises (activities), auxiliary features, and other information. The software programs reviewed are the following: ABECAS--Agri-Business Enterprise Accounting; AccountStar; AgCHECK Financial Recordkeeper; AgCHECK Plus--Financial Management System; AgData General Ledger with Cost Accounting; Agricultural Accounting System; Agro Plus; AgStar; AMS Accounting Program; BASIC ACCOUNTING; C.M.C. General Accounting System; COMFAB; Computerized Personal Accountant; COST MANAGER; C.P.A. of Agriculture; Assistant C.P.A. of Agriculture; Farm Ledger Pro; FAS; The Financial Manager Program; General Ledger; Homestead Farm Management System; Horizon Accounting; Lund Farm Accounting; PC MARS; Red Wing General Ledger; THE TERRA SYSTEM; and Transaction Plus. (KC)